Vulnerability Assessment Website E-Government dengan NIST SP 800-115 dan OWASP Menggunakan Web Vulnerability Scanner - Esti Zakia Darojat; Eko Sediyono; Irwan Sembiring (Universitas Diponegoro, 2022)
E-Government is one of the local government's means of implementing service-oriented values and public information disclosure by providing the local government's official website. Vulnerability Assessment (VA) is a vulnerability assessment method by testing security vulnerabilities to find out all potential critical weaknesses of e-government websites, the aims is to support convenience and service improvement when using e-government websites. The method is using descriptive quantitative to analyze and evaluate security level of both e-government websites based on the NIST SP 800-115 method regarding technical guidelines for testing and assessing information security parameters and OWASP using two web vulnerability scanners. This study is to analyze and evaluate the results of vulnerability scanning on two different types of e-government web, namely the e-government web belonging to the local government and village government, the sample assessment using the semarangkab.go.id website belonging to the local government of Semarang Regency, Central Java Province. and gunungtumpeng.id which is the official e-government website owned by the Gunung Tumpeng Village Government, Suruh District, Semarang Regency, Central Java Province, Indonesia. Hasil penelitian menunjukkan ditemukan persamaan penilaian dalam hal kategori level ancaman dan jumlah kerentanan menggunakan kedua alat web vulnerability scanner, dan hasil yang berbeda terdapat pada durasi, kecepatan pemindaian, dan jenis temuan kerentanan. Kedua parameter OWASP dapat memberikan petunjuk dan penjelasan kompleks untuk membantu pengembang atau pihak pemerintah daerah melakukan pengambilan keputusan mengenai keamanan informasi pada web e-government yang dikelola.